Development of a Walking Assistance Apparatus without Fixation on Legs and Study on the Assistance Effectiveness with Electromyography - IKEHARA, Tadaaki; SATO, Yusuke; ITO, Kazuhisa; NAKAGAWA, Kei; YUSA, Hirokazu; AOKAGE, Yoriyuki; SAEGUSA, Shozo; YUGE, Louis; TANAKA, Eiichirou (TRANSACTIONS OF THE JAPAN SOCIETY OF MECHANICAL ENGINEERS Series C, 2011)
Walking assistance is necessary for elderly and persons who engage a heavy activity. In order to meet the social requests, a walking assistance apparatus used a spatial parallel link mechanism have been newly developed in this research. Without making special constraints on person's legs the proposed apparatus can assist whole legs of a person including soles. To utilize the apparatus for elderly in their life, it has to output the angle velocity same as the data of able bodied person. And the equipped person has to be able to walk in various environments (inclined road and stairs, and so on) at will. Therefore the apparatus was equipped an inclination sensor and an ultrasonic sensor, then the angle of the slope and the size of stairs are measured to generate the control signal. The apparatus was equipped a control unit and lithium-ion batteries, and could drive over one hour period. To stabilize the equipped parson's posture for horizontal direction, leaf springs were attached to prevent over-adduction of hip joint. To examine the effectiveness of the proposed apparatus, the muscle fatigue while walking with wearing the apparatus was evaluated for one hour by mean power frequency (MPF) of the measured data of electromyography. As a result, the MPF wearing the apparatus was on maintenance tendency, while the MPF without wearing the apparatus was shifted from high-frequency range to low-frequency range. Moreover, the muscle activity in walking up the stairs was evaluated by IEMG. Therefore, the effectiveness of the apparatus could be confirmed.